1979
DOI: 10.1002/1097-0142(197901)43:1<360::aid-cncr2820430151>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid granulomatosis.A clinicopathologic study of 152 cases

Abstract: A retrospective study of 152 cases of lymphomatoid granulomatosis (LYG) was undertaken to expand current knowledge about clinical manifestations and therapy, and to identify prognostic indicators in this disease. The major clinical and radiographic features and extra-pulmonary sites of involvement noted in previous studies were essentially confirmed in our study. Adverse prognostic factors included neurologic manifestations, and large numbers of atypical lymphoreticular cells within the pulmonary infiltrate. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
356
1
9

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(371 citation statements)
references
References 31 publications
5
356
1
9
Order By: Relevance
“…The most common site of involvement is the lung, with less frequent involvement of other extranodal sites such as the skin, kidney, liver, and central nervous system (CNS) [55]. Since it was first described in 1972 by Liebow et al [56] and for nearly 2 decades, lymphomatoid granulomatosis was thought to be a T-cell lymphoproliferative disorder because of the predominance of CD4-positive helper T cells and the failure to detect any associated B-cell gene rearrangements [57,58].…”
Section: Ebv-associated B-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…The most common site of involvement is the lung, with less frequent involvement of other extranodal sites such as the skin, kidney, liver, and central nervous system (CNS) [55]. Since it was first described in 1972 by Liebow et al [56] and for nearly 2 decades, lymphomatoid granulomatosis was thought to be a T-cell lymphoproliferative disorder because of the predominance of CD4-positive helper T cells and the failure to detect any associated B-cell gene rearrangements [57,58].…”
Section: Ebv-associated B-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…Major sites of extrapulmonary involvement include kidney (32 %), skin (29 %), liver (29 %) and CNS (26 %) [2]. Upper respiratory tract, gastrointestinal tract, spleen and lymph nodes are rarely affected [3].…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest study so far where they suggested increased prevalence of disease in patients on immunosuppressants, transplant patients and those with already existing autoimmune disorders. Hence, the role of B cell immune dysfunction and the atypical cell belonging to B cell lineage was proposed [3]. In 1990, in another study EBV genome was detected in 29 cases by polymerase chain reaction [4].…”
Section: Discussionmentioning
confidence: 99%
“…Lung is most commonly involved organ (80-90 %) followed by skin up to 50 % and nervous system in 30 %. They may occur together at presentation or in sequential or in isolation [3,4]. Patients may present with constitutional symptoms or related to the organ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 year mortality is 60-90 % [7]. Poor prognostic predictors are age less than 25 years, high grade histology, CNS involvement and presence of hepatomegaly and leukocytosis [3]. Treatment of LYG is not well established owning to its rarity as well as unpredictable course after therapy.…”
Section: Discussionmentioning
confidence: 99%